Routing Innate and Adaptive Immune response against M. tuberculosis and boosting Mycobacterium bovis Bacillus Calmette Güerin (BCG) vaccine immunity through prime boost protocols - G. Guerrero, Gloria; Hernández-Pando, Rogelio (Trends in Immunotherapy, 2023)
Tuberculosis (Tb) is still a global health problem, especially in developing countries. Several factors contribute to this, among them the increasing multidrug resistance strains, the dangerous liaisons with other intracellular pathogens, such as HIV, and more recently, SARS-CoV2 pandemics. There are many aspects that remain to understand the bacterial molecular mechanism of pathogenicity and the immune response induced by the interaction of M. tuberculosis (MTb) with the host. The official and current vaccine based on the attenuated Mycobacterium bovis Bacillus Calmette Guerin (BCG) is protective against several forms of Tb meningitis and Miliary TB or disseminated disease in young children. However, it fails to protect young and adult individuals. There are several new promising candidates for vaccines to replace or boost BCG-induced immunity. Several evidences exist from humans and mice on the role of the trained innate memory of monocytes and NK cells, on the second encounter with the same mycobacterial pathogen or other respiratory pathogens. This type of immune response is nonspecific and independent of the T and B cells. Thus, BCG vaccination is a double immunogen that activate specific immune responses and is also able to stimulate nonspecific immune responses. Here, it is outlined the host immunity against MTb, the potential of BCG vaccination and prime boost protocols for routing innate and adaptive immune responses in TB.